A case study of electric chiller performance bottleneck diagnosis by root cause analysis - Xiaoming, Z. (Institute of Electrical and Electronics Engineers Inc., 2016)
As one of the core cooling equipment in district cooling system, latest electric chiller can achieve high energy efficiency and low CO2 emission. In recent years, many researches have been conducted on cooling plant performance evaluation and anomaly detection, but very few can quantitatively detect root causes of electric chiller's performance anomaly. In the case study at district cooling plant of UTP (Universiti Teknologi PETRONAS), we adapted RCA (Root Cause Analysis) diagnosis method from steam absorption chiller to electric chiller; developed two bottleneck models for electric chiller's COP (Coefficient of Performance) and CHW (CHilled Water supply) performance diagnosis. By applying new RCA models and method to field trial at UTP campus cooling system, we effectively diagnosed the root cause for electric chillers' performance degradation during period from 2014 to 2015. Â© 2016 IEEE.